ANALISIS NOVEL 00.00 KARYA AMEYLIA FALENSIA DITINJAU DARI SEGI KONFLIK BATIN TOKOH LENGKARA TINJAUAN PSIKOLOGI SASTRA - Fara Aulia; Rr. Sulistyawati (Jurnal Ilmiah Global Education, 2023)
Inner conflict arises in everyone, especially when someone faces or chooses between two choices or several possibilities that are generally experienced by the main character in fictional (fictional) stories that are closely related to one's psychology. This article aims to describe and explain aspects of the inner turmoil that the character of Lengkara receives from the people around him in the novel 00.00 by Ameylia Falensia, using the literary psychology approach of Sigmund Freud. This theory explains human development and personality. Sigmund Freud divides aspects of personality structure into three parts, namely: Id, Ego and Superego. This study uses descriptive qualitative research approaches and methods through analysis of the contents of the novel using a literary psychology approach, especially in terms of inner conflict. Data analysis was carried out by covering three components namely; (1) Data reduction; (2) Data Presentation; and (3) Conclusion Drawing. This research can certainly inspire us as readers in responding to this life, even though people are mean to us as much as possible we still have to live and fight for justice for himself, why was he hated so badly by his parents, even the people around him who gradually started to hate him. This novel also contains many implied and explicit messages. Some of them, the importance of the role of the father figure in the life of his daughter and in establishing a relationship should be mutually open so that there are no misunderstandings.